The Training of Writing Classroom Action Research for Teachers in SMA Negeri 1 OKI on 2022 - Fitria, Happy; Lian, Bukman; Mulyadi, Mulyadi; Fitriani, Yessi; Ahyani, Nur; Harapan, Edi; Wahidy, Achmad; Effendi, Darwin (Journal of Social Work and Science Education, 2022)
The target and output of this training is to implement the Tridharma of Higher Education, and writing Classroom Action Research (CAR) for teachers at SMA Negeri 1 OKI. The training methods used are 1) lecturing in which the trainer explains to the trainees what and how to write and publish CAR; and 2) evidence-based learning, where training participants are invited to write together and know how to write CAR. The results obtained from this training can make participants (teachers) 1) write the background of the problem; 2) formulate the problem; 3) write a literature review; 4) writing research methodology; 5) write the results of research and discussion; 6) write conclusions, suggestions and bibliography; and 7) writing abstracts and bibliography.